Case Report: A Novel Intronic Mutation in AIFM1 Associated With Fatal Encephalomyopathy and Mitochondrial Disease in Infant - Peng, Qi; Ma, Keze; Wang, Linsheng; Zhu, Yinghua; Zhang, Yaozhong; Rao, Chunbao; Luo, Dong; Jiang, Zaixue; Lai, Wei; Lu, Huiling; Duan, Chaohui; Zhou, Zhongjun; et al. (Frontiers in Pediatrics, 2022)
Background:The AIFM1 gene is located on chromosome Xq26.1 and encodes a flavoprotein essential for nuclear disassembly in apoptotic cells. Mutations in this gene can cause variable clinical phenotypes, but genotype-phenotype correlations of AIFM1-related disorder have not yet been fully determined because of the clinical scarcity. Case Presentation:We describe a 4-month-old infant with mitochondrial encephalopathy, carrying a novel intronic variant in AIFM1 (NM_004208.4: c.1164+5G>A). TA cloning of the complementary DNA (cDNA) and Sanger sequencing revealed the simultaneous presence of an aberrant transcript with exon 11 skipping (89bp) and a normal transcript through analysis of mRNA extracted from the patient's fibroblasts, which is consistent with direct RNA sequencing results. Conclusion: We verified the pathogenic effect of the AIFM1 c.1164+5G>A splicing variant, which disturbed normal mRNA splicing. Our findings expand the mutation spectrum of AIFM1 and point out the necessity of intronic sequence analysis and the importance for integrative functional studies in the interpretation of sequence variants.